The Role of Blended Education in Developing Attitudes towards learning English language for Sixth Grade Students from The Point of view of Teachers in Jordan - Hiyasat, Shatha Yasser; Abu Sneina, Odeh AbdAlGawad (Journal of Educational and Psychological Sciences, 2023)
This study aimed at revealing the Role of Blended Education in Developing Attitudes towards learning English language for Sixth Grade Students from The Point of view of Teachers in Jordan. To achieve the aim of the study, the analytical descriptive approach has been used according to the variables (experience, qualification, sector). The study population consisted of the female teachers in Ain Al- Basha Province for the 2021/2022 year, the study sample was selected by the random sample method and consisted of (40) of the female teachers in Ain Al- Basha province. (25) of the female teachers are from private schools and (15) of the female teachers are from governmental schools, For the sake of the study A three- part questionnaire was prepared. The questionnaire was checked in terms of its validity and reliability. The results showed that the role of blended education in developing attitudes towards learning English among sixth- grade students from the teachers’ point of view (total score), came to a large extent, as the arithmetic mean of the teachers’ responses was (3.70), and a standard deviation (0.64). The results also showed that there were no statistically significant differences due to the variables (experience, sector, educational qualification). The study recommended, paying attention to the development of sixth- grade students’ attitudes to learning English, as it is an international language in the practical and educational fields. As well as encouraging researchers to conduct more research and studies on the reality of blended education in learning English language courses for the sixth grade and linking them with other variables.